2022
DOI: 10.1007/s12350-020-02514-5
|View full text |Cite
|
Sign up to set email alerts
|

Cardiopulmonary transit time: Reinforcing the case for positron emission tomography after heart transplantation

Abstract: Publisher's Note Springer Nature remains neutral with regard to jurisdictional claims in published maps and institutional affiliations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Since most dedicated software packages for MBF calculation are standardized to place region of interest in left ventricular (LV) cavity to obtain TAC. The actual interval of perfusion tracer passing through LV in clinical dynamic study should be approximately less than two minutes ( 18 ), and this was the primal reason that the acquisition timing was set as 60 sec in our study. Other phantom study for 82 Rb, Renaud et al reported that approximately 3 to 14 MBq/kg dose of radioactivity is recommended as injected dose, and the counting rate should be 4 to 14 Mcps as recommendation ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…Since most dedicated software packages for MBF calculation are standardized to place region of interest in left ventricular (LV) cavity to obtain TAC. The actual interval of perfusion tracer passing through LV in clinical dynamic study should be approximately less than two minutes ( 18 ), and this was the primal reason that the acquisition timing was set as 60 sec in our study. Other phantom study for 82 Rb, Renaud et al reported that approximately 3 to 14 MBq/kg dose of radioactivity is recommended as injected dose, and the counting rate should be 4 to 14 Mcps as recommendation ( 19 ).…”
Section: Discussionmentioning
confidence: 99%